(untitled) - Ladaniya, Milind S. (Amsterdam, 2008)
The Book provides practical tips for post harvest management; Includes all aspects of citrus fruit biology, technology and quality evaluation; Discusses biotechnological applications and potential fresh citrus fruit quality improvement; Evaluates medicinal and therapeutic applications and recent clinical findings; Exhaustive glossary included
Keywords: Citrus fruit,Cây giống cam quýt; biology,technology,đặc tính sinh học,công nghệ chế biến